Antipsoriatic activity of ethanolic extract of morinda reticulata in a novel in vivo screening model (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2022)
The goal of this work was to use an unique in vivo screening strategy to examine the antipsoriatic effect of ethanolic extract of Morinda reticulata (EEMR). For psoriasis induction, 0.1 ml of prepared complete Freund's adjuvant (CFA) & formaldehyde mixture (1:10) was topically administered to the dorsum surface of Swiss albino mice's skin for 7 days. The phenotypic (redness, erythema, and scales) & histological aspects of psoriasis severity index (PSI) were assessed (epidermal thickness). After inducing psoriasis, the therapeutic impact of 0.05 percent and 0.1 percent (w/w) EEMR ointments was examined. The antipsoriatic activity of EEMR ointments was assessed using the PSI and histological investigation after they were applied once daily for three weeks. In animals treated with 0.05 percent and 0.1 percent (w/w) ointments of EEMR, we observed phenotypic and histological features & found a progressive reduction (P 0.05) in the severity of psoriatic lesions (redness, erythema, & scales) from day 7 to day 21 as well as decreased epidermal thickness. The findings revealed that 0.1 percent (w/w) EEMR ointments have dose-dependent therapeutic effects in CFA & formaldehyde-induced psoriasis. The current study discovered that M.reticulata  has substantial antipsoriatic activity and can be used to treat psoriasis.